Financial Literacy Level Of Gojek Drivers In Malang City Online Loans User As An Effort To Improve Welfare - Arif Amrullah; Sugeng Hadi Utomo; Nasikh Nasikh (FKIP, Universitas Palangka Raya, 2023)
This study aims to determine the level of financial literacy and the level of financial inclusion of Gojek drivers who use online loans in Malang City. As well as knowing financial literacy and inclusion as an effort to improve welfare. This study uses a phenomenological approach with the assumption of a constructivist philosophy. This study also uses a qualitative descriptive approach which is a method based on post-positivism philosophy. The instrument used uses a survey with 100 Gojek driver participants in Malang City. The results of the study show that the literacy of Gojek drivers in Malang City is measured at a level of 67.92% which indicates a moderate level with only 7% having a high literacy level. Meanwhile, the inclusion level of Gojek drivers in Malang City is measured at a level of 66.83%. There is a gap of 19.7% with the average inclusion rate in Malang City. It also shows that only 7% have a high level of financial inclusion. There are 2% of Gojek drivers in Malang City, each of whom has a high level of financial literacy and inclusion. Other results show that 88% are declared prosperous under the UMR category, and 84% are also declared prosperous by calculating the income exchange rate. Subjectively, 91% are categorized as prosperous with the highest indicator being family harmony at 73%. Followed by a good living environment by 60%. However, housing and asset indicators are considered low at only 37%.